HEALTH PROMOTION THROUGH INTERACTIVE VIDEO MEDIA TO INCREASE WOMEN'S KNOWLEDGE AND RESILIENCE DURING THE COVID-19 PANDEMIC IN TRIHARJO VILLAGE, PANDAK, BANTUL - Venny Vidayanti; Deden Iwan Setiawan; Aan Umbu Tay Parwana (Jurnal Keperawatan Respati Yogyakarta, 2022)
The Maternal Mortality Rate (MMR) in Bantul Regency has risen in 2020. Triharjo Village has the highest percentage of high-risk pregnant women in the Pandak II Health Center's target region (30.48%). Currently, insufficient information sources for pregnant women can promote stress, anxiety, and low maternal awareness, increasing the chance of exposure to Covid-19. During the COVID-19 pandemic, effective promotional media are needed to increase pregnant women's knowledge and resilience. This study will measure the effect of interactive video media in increasing pregnant women's knowledge and resilience to the COVID-19 pandemic. The research design is a quasi-experiment using consecutive sampling. The study sample comprised of 38 pregnant women who satisfied the criteria. The knowledge instrument was modified based on the literature review WHO recommendation, POGI and construct validity test was carried out while the resilience instrument uses the Connor-Davidson Resilience Scale (CD-RISC). This study used paired t-tests to determine the effectiveness of the intervention. The results of the paired t-test for knowledge of pregnant women showed p-value of 0.000 <0.05 and p-value of the effect of interactive video education on resilience of pregnant women. of 0.000 < 0.05. This study concluded that interactive video media can increase pregnant women's awareness and resistance during the Covid-19 pandemic.